1992
DOI: 10.1007/bf01605979
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme and immunohistochemistry on undecalcified bone and bone marrow biopsies after embedding in plastic: A new embedding method for routine application

Abstract: A simplified method of low temperature methyl and butyl methacrylate embedding (up -20 degrees to -15 degrees C) is demonstrated using a proper redox system of benzoyl peroxide and aromatic amine. This method combines the morphological superiority of plastic-embedded bone tissue and bone marrow sections with the advantages of specific enzyme histochemical and immunochemical markers. The method permits good preservation of morphological details, the survival of antigenic determinants and the retention of enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(56 citation statements)
references
References 19 publications
1
55
0
Order By: Relevance
“…Infiltrated specimens were placed into embedding molds, and polymerization was performed at Ϫ15°C. 12 Polymerized blocks were initially ground to bring the tissue components closer to the cutting surface. After the opposite side of the block was glued to a Plexiglas slide with Technovit 4000 (Kulzer & Co) in vacuum, a 1200-grit grinding in a micro parallel grinding system (EXAKT, Apparatebau) was used, followed by 4000-grit sandpaper grinding, which smoothed the final lower surface of the samples.…”
Section: Methodsmentioning
confidence: 99%
“…Infiltrated specimens were placed into embedding molds, and polymerization was performed at Ϫ15°C. 12 Polymerized blocks were initially ground to bring the tissue components closer to the cutting surface. After the opposite side of the block was glued to a Plexiglas slide with Technovit 4000 (Kulzer & Co) in vacuum, a 1200-grit grinding in a micro parallel grinding system (EXAKT, Apparatebau) was used, followed by 4000-grit sandpaper grinding, which smoothed the final lower surface of the samples.…”
Section: Methodsmentioning
confidence: 99%
“…Animals received daily aspirin (Ϸ40 mg, orally), beginning on Day Ϫ3 and continuing until euthanasia. On Day 1, animals received a single prophylactic injection of benzathine/procaine penicillin-G (42 000 IU/kg, IM) and were preanesthetized (ketamine HCl, 10 mg/kg, IM; atropine SO 4 , 0.04 mg/kg, IM), then intubated and maintained in anesthesia with isoflurane. Animals were euthanized at day 4 (nϭ2), day 7 (nϭ2), and day 14 (nϭ2) after injury.…”
Section: Surgical and Tissue Retrieval Techniquesmentioning
confidence: 99%
“…Stented segments were embedded in methyl methacrylate mixed with n-butyl methacrylate (Sigma Chemical Co) 4,5 to allow for sectioning through metal stent struts. Balloon-injured segments were paraffin embedded.…”
Section: Tissue Processingmentioning
confidence: 99%
“…Erben nants are lost because of temperature peaks and modification of chemical structures in the tissue by reactive radicals formed during polymerization of MMA (Baskin et al 1992;Wolf et al 1992). It is also possible to initiate polymerization of methacrylates by blue or uv light photons.…”
mentioning
confidence: 99%
“…Recently, an MMA embedding technique has been reported that can be used for embedding of larger bone samples, and which preserves enzyme activities and antigenic determinants in bone tissue (Wolf et al 1992). This embedding mixture polymerizes at Ϫ 15 to Ϫ 20C.…”
mentioning
confidence: 99%